What Works and for Whom? Effectiveness and Efficiency of School Capital Investments across the U.S. - Barbara Biasi; Julien Lafortune; David Schönholzer (Institute of Labor Economics (IZA), 2024)
This paper identifies which investments in school facilities help students and are valued by homeowners. Using novel data on school district bonds, test scores, and house prices for 29 U.S. states and a research design that exploits close elections with staggered timing, we show that increased school capital spending raises test scores and house prices on average. However, impacts differ vastly across types of funded projects. Spending on basic infrastructure (such as HVAC) or on the removal of pollutants raises test scores but not house prices; conversely, spending on athletic facilities raises house prices but not test scores. Socio-economically disadvantaged districts benefit more from capital outlays, even conditioning on project type and the existing capital stock. Our estimates suggest that closing the spending gap between high- and low-SES districts and targeting spending towards high-impact projects may close as much as 25% of the observed achievement gap between these districts.
Keywords: H41; H75; I22; I24; R30; R53; 330; test scores; school capital; school expenditures; real estate